Simbolisme Sufistik dalam Musik Populer: Studi pada Lirik Lagu Noe Letto dalam Pandangan Eero Tarasti - Ida Nursida; Hatta Raharja (Language Development Center, 2025)
Background: Song lyrics serve as a medium for reflecting on a composer's spiritual and existential journey. There is a need to understand how Sufi symbolism constructs the concept of self (Dasein) and its relationship with the Transcendent. Purpose: This study aims to examine the Sufi symbolism in Noe Letto’s songs “Sebelum Cahaya” and “Sandaran Hati,” focusing on how he reflects his existentialism to construct Dasein and Transcendence using Eero Tarasti’s existential semiotics. Method: This qualitative study employs Eero Tarasti’s existential semiotics as the main analytical framework to examine Sufistic symbolism in Noe Letto’s song lyrics. The analysis focuses on two selected works, “Sebelum Cahaya” and “Sandaran Hati”, using lyric-based qualitative data to trace how symbols articulate dimensions of Dasein and Transcendence. Results and Discussion: The findings of this study indicate that Noe Letto, through his lyrics, effectively reflects his Sufi journey. He successfully illustrates the concept of Dasein (self-existence) while connecting himself to the transcendent domain. Further discussion indicates that Noe Letto is able to strengthen the bond between God and humans, making the relationship feel close and affectionate. Although this study is limited to two song lyrics, these findings provide deep insight into the mechanisms a composer uses to articulate his spiritual journey to achieve transcendence. Conclusions and Implications: In conclusion, this study confirms that a composer's creative process is a unique and authentic means of self-expression. Consequently, this article contributes to a new theoretical understanding of the significance of a composer's work and offers a method for deducing (obtaining) the existential meaning of song lyrics.